Gainsharing and Organizational Learning: An Analysis of Employee Suggestions Over Time - Arthur, Jeffrey B.; Aiman‐Smith, Lynda (Academy of Management Journal, 2001)
The authors propose a model of gainsharing as an organizational learning system. Analyzing employee suggestions submitted over the first four years of a gainsharing plan at one plant, the authors found that although conventional explanations of how gainsharing works predicted changes in the volume of total suggestions, changes in their content were consistent with an organizational learning process. Suggestions indicating ?first-order learning? were initially high but declined over time as a percentage of total suggestions, and suggestions congruent with ?second-order learning? became a larger portion of the total suggestions over time.